Shaping public spaces from below: the vernacular semiotics of Leeds Kirkgate Market. Issue 1 (1st January 2020) - Adami, Elisabetta
ABSTRACT: The paper presents a social semiotic approach to vernacular sign-making in place, by examining the visual landscape of Leeds Kirkgate Market, as an example of a semiotically-unregulated place. Traders have ample freedom of self-expression and agency in shaping their stalls through all visual-material resources (beyond mere signage, as analysed in linguistic landscape research). There derives a composite non-cohesive aesthetic of the market's visual landscape, driven by the situated needs and tastes of the socio-culturally diverse population inhabiting the place. The resulting semiotic diversity is remarkable when compared to its neighbouring areas, as well as to recently renovated UK city markets. Against an increased institutional regulation of urban landscapes, semiotically-unregulated places enable vernacular practices from below that defy current aesthetic tenets in professional design and help revealing and questioning the power dynamics underlying a social construction of taste. Research into vernacular semiotics shows the enhanced cultural richness resulting from people's agency in shaping the public spaces in which they live.